The Exploitation and Sustainable Development of Yunnan’s Tourism Culture Resource - Rao , Ruiying (Journal of Sinology (วารสารจีนวิทยา), 2011)
Yunnan is a main tourism province where tourism resources are abundant. Apart from the natural tourism resources, ethnic culture is a kind of important tourism resources which is named tourism culture resources. During the course of the development of tourism industry, ethnic culture is being developed and integrated which is playing an important role in the development of the economics, tourism and culture. However, ethnic traditional culture should be protected in the tourism development process, in order to avoid the damage in ethnic ecological culture which resulted from the overexploitation. Optimization combination between culture and tourism should be improved by scientific conservation and rational exploitation and lead to the success of the sustainable development of tourism industry. Finally, during the course of sustainable development of tourism culture resources, intellectual support, financial support and systemic security should be provided by the government who will play a crucial role.